The Influence of Corporate Social Responsibility, Net Working Capital, and CEO Duality on Cash Holding - Ilmiani, Amalia; Mutmainah, Dinda Maulin; Ardiyani, Komala; Mahmudah, Dinda Amalia (AJAR, 2025)
This Study aims to determine the effect of corporate social responsibility (CSR), net working capital (NWC), and CEO Duality in banking sub-sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The data collection method used is purposive sampling, with a total sample of 25 banking companies listed on the Indonesia stock exchange from 2018 to 2022. Data analysis in this research was conducted using Partial Least Square (PLS) – Structural Equation Modeling (SEM). The results of this study are corporate social responsibility has a negative infuence on cash holding, net working capital has a positive influence on cash holding and ceo duality has a negative influence on cash holding.